Community Communication Strategy Bangun Raya in Maintaining Harmony Between NU and Muhammadiyah Religious Groups - Roni Apriadi; Akhmad Rifa'i (Edumaspul: Jurnal Pendidikan, 2024)
Communication is the process of sending and receiving messages. The purpose of communication is for the communicator to do what is intended in the message. Communication can be successful when people perceive the closeness or similarity of the communication message. Otherwise, conflicts will arise. Conflict affects harmony. Conflict can strengthen harmony or divide a nation. Strategies in communication are needed to facilitate the communication process, especially in communication between cultures or religions. Culture and religion are very prone to conflict, so communication between cultures or religions is very necessary in Indonesia because the Indonesian language is very diverse. In other words, the function of communication is to maintain multicultural or multireligious harmony. The aim of this research is to determine the communication strategies of the Bangun Raya community in maintaining harmony between the NU and Muhammadiyah religious groups. Apart from that, this research is qualitative in nature. Data collection was carried out observationally, by making observations at the research location. regarding data analysis, starting from data collection, data reduction, data presentation to drawing conclusions. The results of this research show that the communication strategies carried out by the NU and Muhammadiyah community in Bangun Raya are intrapersonal communication, interpersonal communication, group communication and intercultural communication. Apart from that, there are also four factors that can strengthen relations between these two religious groups, namely Muhammadiyah and NU, namely awareness of differences in understanding, a high level of meeting, and the existence of kinship relations.